Aramid nanofiber interface layer modified zinc metal material and application thereof as aqueous zinc ion battery negative electrode material

By modifying the hydrophobic, zinc-friendly, and three-dimensional porous aramid nanofiber interface layer on the zinc metal material, the problem of poor stability of zinc metal negative electrode in aqueous zinc ion batteries is solved, and the battery cycle life is significantly extended and the zinc dendrites are inhibited.

CN119634202AActive Publication Date: 2025-03-18ANHUI UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510161779.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-18
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

The zinc metal negative electrode in aqueous zinc ion batteries has poor stability, resulting in the formation and growth of zinc dendrites, causing battery short circuits and capacity decline.

Method used

The zinc metal material is modified by aramid nanofiber interface layer. By constructing a hydrophobic, zinc-philic, and three-dimensional porous interface layer, it isolates the direct contact between water molecules and zinc metal, enhances the Zn2+ kinematic mechanics and uniform zinc ion flux.

Benefits of technology

It significantly improves the stability of zinc metal materials, extends the cycle life of aqueous zinc ion batteries, reduces the occurrence of water-induced side reactions, and inhibits the formation and growth of zinc dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119634202A_ABST
    Figure CN119634202A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc metal material modified by an aramid nanofiber interface layer and application of the zinc metal material as a negative electrode material of an aqueous zinc ion battery, and belongs to the technical field of new materials and zinc ion batteries, a preparation method comprises the following steps: (1) ultrasonically cleaning the surface of a zinc foil by adopting absolute ethyl alcohol, and drying to obtain a pretreated zinc foil; and (2) uniformly blade-coating the pretreated zinc foil with the aramid nanofiber solution, and ventilating and drying to obtain the zinc metal material with the surface modified by the aramid nanofiber interface layer. According to the preparation method, direct contact between water molecules and zinc metal is isolated by constructing a hydrophobic, zinc-loving and three-dimensional porous interface layer, Zn < 2 + > transport kinematics is enhanced, and zinc ion flux is uniform, so that water-induced side reactions are reduced, formation and growth of zinc dendrites are inhibited, the zinc metal material shows excellent stability, and the service life of the zinc metal material is prolonged. Great development potential and application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials and zinc ion batteries, specifically to the technical field of aramid fiber materials and aqueous zinc ion batteries, and in particular to a zinc metal material modified with an aramid nanofiber interface layer and its application as a negative electrode material for aqueous zinc ion batteries. Background Art

[0002] Lithium-ion batteries in electrochemical energy storage devices are widely used in new energy vehicles, digital products and other equipment due to their high energy density and environmental friendliness. However, the large-scale development of lithium-ion batteries is constrained by the bottlenecks of high lithium prices, high risk, and harsh battery production conditions. For example, most lithium-ion batteries use organic solutions as electrolytes, which can easily cause batteries to catch fire and explode. In view of the above-mentioned problems in the production and use of lithium-ion batteries, researchers have focused their attention on aqueous batteries. Aqueous batteries use aqueous solutions as electrolytes, which are flame retardant, can effectively prevent battery spontaneous combustion and explosion, and have strong safety. At the same time, the price of aqueous solution electrolytes is lower than that of organic solution electrolytes for lithium-ion batteries, and the ionic conductivity of aqueous solution electrolytes is much higher than that of organic solution electrolytes.

[0003] Zinc metal as a negative electrode of the battery has low cost, high safety, and high theoretical specific capacity (820 mAh g) compared with other metals. −1 ) and low redox potential (-0.76 V vs. standard hydrogen electrode). However, the inherent problems of zinc metal itself limit the practical application of aqueous zinc-ion batteries. When it is applied to the negative electrode of aqueous zinc-ion batteries, uneven zinc deposition will lead to the formation and growth of zinc dendrites, which will pierce the diaphragm and eventually cause the battery to short-circuit. Zinc dendrites have mechanical rigidity and structural heterogeneity, and they are easy to fall off from the zinc negative electrode to form "dead zinc", resulting in a reduction in active materials and battery capacity decay. In addition, the occurrence of water-induced side reactions such as hydrogen evolution, corrosion, and passivation leads to reduced battery stability. The above adverse electrochemical reactions limit the development and application of aqueous zinc-ion batteries. Summary of the invention

[0004] Aiming at the problem of poor stability of zinc metal negative electrode in aqueous zinc ion battery, the present invention provides a zinc metal material modified with aramid nanofiber interface layer and its application as negative electrode material of aqueous zinc ion battery, which can isolate water molecules from direct contact with zinc metal by constructing hydrophobic, zinc-philic and three-dimensional porous interface layer, thereby enhancing Zn 2+ The transport kinetics and uniform zinc ion flux can reduce the occurrence of water-induced side reactions, inhibit the formation and growth of zinc dendrites, and make zinc metal materials show excellent stability, which has great development potential and application prospects.

[0005] In order to achieve the above object, the present invention adopts a method for preparing a zinc metal material modified with an aramid nanofiber interface layer, comprising the following steps: (1) using anhydrous ethanol to clean the surface of the zinc foil by ultrasonic cleaning and drying to obtain a pretreated zinc foil; (2) evenly coating the aramid nanofiber solution on the pretreated zinc foil and drying it under ventilation to obtain a zinc metal material with an aramid nanofiber interface layer modified on the surface; Wherein, the aramid nanofiber solution is prepared by the following steps: (a) Place PPTA and KOH in a beaker, add DMSO solution and deionized water, and stir; (b) continuing to add deionized water and stirring, filtering the stirred solution to collect the aramid nanofibers; (c) dispersing the aramid nanofibers in deionized water, vacuum filtering, collecting the aramid nanofibers and re-dispersing them in anhydrous ethanol, vacuum filtering again, and collecting the aramid nanofibers; repeating step (c) multiple times; (d) The collected aramid nanofibers are dispersed in anhydrous ethanol to obtain an aramid nanofiber solution.

[0006] As an improvement, in the step (1), the temperature of ultrasonic cleaning is 20-30°C, and the time of ultrasonic cleaning is 15-30 minutes; vacuum drying is adopted, the drying temperature is 45-60°C, and the drying time is 10-30 minutes.

[0007] As an improvement, the concentration of the aramid nanofiber solution in step (2) is 1.5-3 mg / mL.

[0008] As an improvement, the mass ratio of PPTA to KOH in step (a) is 1:(1-3).

[0009] As an improvement, in step (a), the mass volume ratio of PPTA to DMSO solution is 1 g: (400-600) ml, and the mass volume ratio of PPTA to deionized water is 1 g: (15-25) ml; in step (b), deionized water is added in an amount of 2-3 times the volume of the DMSO solution, and the stirring time is 2-4 h.

[0010] As an improvement, a filter membrane with a pore size of 0.22 µm is used in step (b) and step (c).

[0011] The second aspect of the present invention also provides a zinc metal material modified with an aramid nanofiber interface layer, which is prepared by the preparation method, wherein the thickness of the aramid nanofiber interface layer is 1-3 µm, and the aramid nanofiber interface layer is a three-dimensional porous structure with abundant and uniform pores.

[0012] The third aspect of the present invention also provides an application of the zinc metal material modified with the aramid nanofiber interface layer as a negative electrode material for an aqueous zinc ion battery.

[0013] As an improvement, the aqueous zinc ion battery is a zinc-zinc symmetrical battery, which includes a zinc sheet positive electrode, a zinc sheet negative electrode, a ZnSO 4 The electrolyte and the glass fiber separator are provided, and the zinc sheet negative electrode is punched out of a zinc metal material modified by an aramid nanofiber interface layer.

[0014] As an improvement, the aqueous zinc ion battery is obtained by the following steps: using a punching machine to punch the prepared aramid nanofiber interface layer modified zinc metal material into a pole piece with a diameter of 12 mm, and assembling in the order of anode shell, spring, gasket, cathode, GF / D standard glass fiber diaphragm, cathode, gasket, cathode shell, wherein 80-100 μL 2M ZnSO is added to the diaphragm. 4 The electrolyte is packaged into a button battery using a button battery packaging machine.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) When the zinc metal material modified by the aramid nanofiber interface layer of the present invention is used in a zinc-zinc symmetric battery, the −2 、1 mAh cm −2 Under the test conditions, the stable cycle lasted for more than 2000 hours, which is more than 13 times the cycle life of the zinc-zinc symmetric battery using bare zinc electrodes (about 135 hours), showing excellent stability.

[0016] (2) The zinc metal material modified by the aramid nanofiber interface layer of the present invention is hydrophobic and can serve as a physical barrier to prevent water in the electrolyte from directly contacting the zinc negative electrode, thereby inhibiting the occurrence of water-induced side reactions such as corrosion, hydrogen evolution, and passivation, thereby achieving an improvement in the cycle performance of the aqueous zinc ion battery.

[0017] (3) The zinc metal material modified by the aramid nanofiber interface layer of the present invention has abundant nucleophilic carbonyl functional groups, which have high zinc affinity and can adjust the solvation configuration to accelerate the Zn 2+ desolvation, thereby enhancing its transport kinetics.

[0018] (4) The zinc metal material modified with the aramid nanofiber interface layer of the present invention has a three-dimensional nanoporous structure. The uniform pores formed by the interlaced and stacked fibers can serve as ion channels for zinc ion transmission, uniform zinc ion flux, and reduce the uneven deposition of zinc ions, thereby inhibiting the formation and growth of zinc dendrites, and significantly extending the cycle life of the aqueous zinc ion battery.

[0019] (5) The present invention washes the aramid nanofibers with water and anhydrous ethanol for multiple times, removes the residual KOH solution by washing with water, removes the residual DMSO solution and water by washing with anhydrous ethanol, and finally disperses the collected aramid nanofibers in anhydrous ethanol to make the aramid nanofibers more evenly dispersed, thereby ensuring that the aramid nanofiber solution can be evenly scraped onto the pretreated zinc foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the contact angle of the bare zinc metal of Example 1; Figure 2 The contact angle of the zinc metal material modified by the aramid nanofiber interface layer of Example 1 of the present invention; Figure 3 This is a SEM image of the zinc metal material modified by the aramid nanofiber interface layer of Example 1 of the present invention; Figure 4 The molecular formula and schematic diagram of the aramid nanofiber used in Example 1 of the present invention; Figure 5 This is a statistical diagram of the diameter distribution of the aramid nanofibers used in Example 1 of the present invention; Figure 6 This is a statistical diagram of the pore size distribution of the aramid nanofiber interface layer of Example 1 of the present invention; Figure 7 This is a SEM image of a cross section of a zinc metal material modified with an aramid nanofiber interface layer according to Example 1 of the present invention; Figure 8 This is an optical top view comparison diagram of the zinc metal material modified with the aramid nanofiber interface layer of Example 1 of the present invention and three groups of zinc metal materials modified with the aramid nanofiber interface layer not prepared according to the method of Example 1; Fig. 9 for Figure 8 Comparison of the bonding degree of two groups of zinc metal materials modified with aramid nanofiber interface layers; Fig.10 is a schematic diagram of the aramid nanofiber solution of Example 1 of the present invention; Fig.11 XRD pattern of the zinc metal material modified by the aramid nanofiber interface layer of Example 1 of the present invention; Fig.12 It is a comparison chart of symmetrical battery cycle stability tests of bare zinc and the zinc metal material modified with the aramid nanofiber interface layer of the present invention. DETAILED DESCRIPTION

[0021] The following embodiments are further descriptions of the content of the present invention as an explanation of the technical content of the present invention, but the essential content of the present invention is not limited to the following embodiments. Ordinary technicians in this field can and should know that any simple changes or replacements based on the essential spirit of the present invention should fall within the scope of protection required by the present invention. Example 1

[0022] A method for preparing a zinc metal material modified with an aramid nanofiber interface layer comprises the following steps: S1. Place 0.5 g PPTA (aramid nanofiber) and 0.75 g KOH in a beaker, add 250 mL DMSO solution and 10 mL deionized water, stir magnetically for 12 h, then add 500 mL deionized water to the beaker and stir for 4 h. S2, using a vacuum filtration device to filter the solution obtained in step S1, using a water filter membrane with a pore size of 0.22 µm, and collecting the dried aramid nanofibers from the filter membrane; S3, the aramid nanofibers obtained in step S2 are completely dispersed in deionized water, vacuum filtered using a water filter membrane with a pore size of 0.22 µm, and the dried aramid nanofibers are collected from the filter paper, and then completely dispersed in anhydrous ethanol, and vacuum filtered using a PVDF membrane with a pore size of 0.22 µm, and the dried aramid nanofibers are collected from the filter paper; step S3 is repeated five times; S4. Disperse the dried aramid nanofibers in 250 mL of anhydrous ethanol and calibrate the solution to obtain an aramid nanofiber solution with a concentration of 2 mg / mL. The obtained aramid nanofiber solution is as follows: Fig.10 As shown, it is light yellow; S5. Place the cut commercial zinc foil in a beaker filled with sufficient anhydrous ethanol, place it in an ultrasonic cleaning machine, and ultrasonically clean it at 25°C for 30 min. Then place it in a vacuum drying oven with a preset temperature of 45°C and dry it for 30 min. S6. Use a scraper to evenly scrape the aramid nanofiber solution obtained in step S4 onto the pretreated zinc foil, place it in a ventilated place to dry, and after the solvent is completely evaporated, obtain a zinc metal material with an aramid nanofiber interface layer modified on the surface.

[0023] Figure 1 The contact angle of the bare zinc electrode test is 85.2°; Figure 2The contact angle of the zinc metal material modified with the aramid nanofiber interface layer (AANF@Zn) was tested to be 110.2°. It can be concluded that compared with bare zinc, the zinc metal material modified with the aramid nanofiber interface layer is hydrophobic, which can act as a physical barrier to prevent water molecules in the electrolyte from directly contacting the zinc metal, thereby inhibiting the occurrence of water-induced side reactions such as corrosion, hydrogen evolution, and passivation.

[0024] Figure 3 This is the SEM image of the zinc metal material modified by the aramid nanofiber interface layer. It can be seen that the interface layer is formed by the interweaving and stacking of aramid nanofibers, which has abundant and uniform pores. These pores can serve as uniform channels for the transmission of zinc ions. The uniform channels promote the uniform flux of zinc ion transport, thereby making the zinc ions uniformly deposited, avoiding the uneven tip effect caused by uneven zinc ion deposition, and effectively inhibiting the formation and growth of zinc dendrites.

[0025] Figure 4 It is the molecular formula and schematic diagram of aramid nanofibers. From its molecular formula, it can be seen that aramid nanofibers have abundant nucleophilic carbonyl functional groups, which have high zinc affinity and can adjust the solvation configuration to accelerate Zn 2+ desolvation, thereby enhancing its transport kinetics.

[0026] Figure 5 This is the statistical distribution diagram of the diameter of aramid nanofibers. The average diameter of the fiber is 14.1 nm. Figure 6 This is a statistical distribution diagram of the pore size of the aramid nanofiber interface modification layer. It can be seen from the figure that the interface layer has a uniform pore size.

[0027] Figure 7 This is a SEM image of the cross-section of the zinc metal material modified with an aramid nanofiber interface layer. The thickness of the aramid nanofiber interface layer is 2.2 µm. It has strong adhesion to the zinc metal and is tightly bonded and not easy to fall off. The aramid nanofiber interface layer is formed by interlaced and stacked fibers, so it exhibits a three-dimensional porous structure with abundant and uniform pores.

[0028] Figure 8 The optical top view comparison diagram of the zinc metal material modified by the aramid nanofiber interface layer of Example 1 of the present invention and three groups of zinc metal materials modified by the aramid nanofiber interface layer not prepared according to the method of Example 1; wherein, a is to disperse the aramid nanofiber directly in deionized water without washing; b is to disperse the aramid nanofiber directly in anhydrous ethanol without washing; c is to disperse the aramid nanofiber in deionized water after five cycles of washing (first with deionized water, then with anhydrous ethanol); d is to disperse the aramid nanofiber in anhydrous ethanol after five cycles of washing (first with deionized water, then with anhydrous ethanol) (i.e., using the method of Example 1); Then, referring to the method recorded in the existing literature, the zinc metal with the aramid nanofiber interface layer is folded and then unfolded, and then the zinc metal is bent again and then restored, and the adhesion between the aramid nanofiber interface layer and the zinc metal is judged by the integrity of the aramid nanofiber interface layer; Combination Figure 8 , comparing a and c, b and d, all show that the effect of the zinc metal material modified by the aramid nanofiber interface layer prepared after washing has been improved. And from the comparison between c and d, it can be seen that the fiber distribution on the zinc metal material (AANF@Zn) modified by the aramid nanofiber interface layer prepared by dispersing the aramid nanofiber in anhydrous ethanol is more uniform, and there is no fiber agglomeration on the surface, while the fiber distribution on the zinc metal material (WANF@Zn) modified by the aramid nanofiber interface layer prepared by dispersing the aramid nanofiber in deionized water is uneven, and there is obvious agglomeration.

[0029] Fig. 9 yes Figure 8 Comparison of the degree of bonding between the two groups of aramid nanofiber interface layers and zinc metal materials ( Fig. 9 (1) Correspondence Figure 8 Middle d, Fig. 9 (2) Correspondence Figure 8 As shown in figure c), after folding and unfolding, the aramid nanofiber interface layer in figure d is tightly combined with the zinc metal material and does not fall off, while the aramid nanofiber interface layer in figure c falls off. The two are further bent and restored, and the aramid nanofiber interface layer in figure d is still tightly combined with the zinc metal material and does not fall off, while the aramid nanofiber interface layer in figure c falls off further, indicating that the aramid nanofiber interface layer prepared by the present invention is tightly combined with the zinc metal material and is not easy to fall off.

[0030] Fig.11 This is the XRD pattern of zinc metal material modified by aramid nanofiber interface layer, which is consistent with the standard PDF card of zinc metal, indicating that the addition of this interface layer has no effect on zinc metal. Example 2

[0031] A method for preparing a zinc metal material modified with an aramid nanofiber interface layer comprises the following steps: S1. Place 0.5 g PPTA and 0.75 g KOH in a beaker, add 300 mL DMSO solution and 12.5 mL deionized water, stir magnetically for 10 h, then add 750 mL deionized water to the beaker and stir for 2 h. S2, using a vacuum filtration device to filter the solution obtained in step S1, using a water filter membrane with a pore size of 0.22 µm, and collecting the dried aramid nanofibers from the filter membrane; S3, the aramid nanofibers obtained in step S2 are completely dispersed in deionized water, vacuum filtered using a water filter membrane with a pore size of 0.22 µm, and the dried aramid nanofibers are collected from the filter paper, and then completely dispersed in anhydrous ethanol, and vacuum filtered using a PVDF membrane with a pore size of 0.22 µm, and the dried aramid nanofibers are collected from the filter paper; step S3 is repeated four times; S4, dispersing the drained aramid nanofibers in 250 mL of anhydrous ethanol and calibrating the solution to obtain an aramid nanofiber solution with a concentration of 2 mg / mL; S5. Place the cut commercial zinc foil in a beaker filled with sufficient anhydrous ethanol, place it in an ultrasonic cleaning machine, and ultrasonically clean it at 20°C for 20 min. Then place it in a vacuum drying oven with a preset temperature of 50°C and dry it for 30 min. S6. Use a scraper to evenly scrape the aramid nanofiber solution obtained in step S4 onto the pretreated zinc foil, place it in a ventilated place to dry, and after the solvent is completely evaporated, obtain a zinc metal material with an aramid nanofiber interface layer modified on the surface. Example 3

[0032] A method for preparing a zinc metal material modified with an aramid nanofiber interface layer comprises the following steps: S1. Place 0.5 g PPTA and 1 g KOH in a beaker, add 250 mL DMSO solution and 7.5 mL deionized water, stir magnetically for 12 h, then add 500 mL deionized water to the beaker and stir for 3 h. S2, using a vacuum filtration device to filter the solution obtained in step S1, using a water filter membrane with a pore size of 0.22 µm, and collecting the dried aramid nanofibers from the filter membrane; S3, the aramid nanofibers obtained in step S2 are completely dispersed in deionized water, vacuum filtered using a water filter membrane with a pore size of 0.22 µm, and the dried aramid nanofibers are collected from the filter paper, and then completely dispersed in anhydrous ethanol, and vacuum filtered using a PVDF membrane with a pore size of 0.22 µm, and the dried aramid nanofibers are collected from the filter paper; step S3 is repeated six times; S4, dispersing the drained aramid nanofibers in 250 mL of anhydrous ethanol and calibrating the solution to obtain an aramid nanofiber solution with a concentration of 2 mg / mL; S5. Place the cut commercial zinc foil in a beaker filled with sufficient anhydrous ethanol, place it in an ultrasonic cleaning machine, and ultrasonically clean it at 30°C for 20 min. Then place it in a vacuum drying oven with a preset temperature of 55°C and dry it for 20 min. S6. Use a scraper to evenly scrape the aramid nanofiber solution obtained in step S4 onto the pretreated zinc foil, place it in a ventilated place to dry, and after the solvent is completely evaporated, obtain a zinc metal material with an aramid nanofiber interface layer modified on the surface. Example 4

[0033] The zinc metal material modified with the aramid nanofiber interface layer prepared in Example 1 is used as the negative electrode to prepare a zinc-zinc symmetric battery, comprising the following steps: The prepared aramid nanofiber interface layer modified zinc metal material was punched into a 12 mm diameter electrode sheet using a punching machine and assembled in the order of negative electrode shell, spring, 0.5 mm gasket, negative electrode, GF / D standard glass fiber separator, positive electrode, 0.5 mm gasket, and positive electrode shell. 90 µL 2M ZnSO 4 The electrolyte is packaged into a button battery using a button battery packaging machine.

[0034] Fig.12 It is a symmetrical button cell composed of a bare zinc electrode and a zinc metal anode modified with an aramid nanofiber interface layer. −2 The surface current density and 1 mAh cm −2 The comparison chart of cycle performance under the surface capacity test conditions shows that the life of the button symmetrical battery using bare zinc electrode is about 135 h, which is much shorter than the 2100 hours of the present invention, indicating that zinc metal does show excellent cycle stability after being modified with aramid nanofiber interface layer.

[0035] The present invention constructs a hydrophobic, zinc-philic, three-dimensional porous interface layer to isolate water molecules from direct contact with zinc metal, thereby enhancing the Zn 2+ The transport kinetics and uniform zinc ion flux can reduce the occurrence of water-induced side reactions, inhibit the formation and growth of zinc dendrites, and make zinc metal materials show excellent stability, which has great development potential and application prospects.

[0036] It should be noted that the above-described embodiments of the present invention are only explanations and clarifications for those skilled in the art to understand the technical essence of the present invention, so the technical contents described are not intended to limit the substantial protection scope of the present invention. The substantial protection scope of the present invention shall be subject to the claims. Those skilled in the art should know that any modifications, equivalent substitutions and improvements based on the substantial spirit of the present invention shall be within the substantial protection scope of the present invention.

Claims

1. A method for preparing a zinc metal material modified with an aramid nanofiber interface layer, characterized in that: The following steps are involved: (1) using anhydrous ethanol to clean the surface of the zinc foil by ultrasonic cleaning and drying to obtain a pretreated zinc foil; (2) evenly coating the aramid nanofiber solution on the pretreated zinc foil and drying it under ventilation to obtain a zinc metal material with an aramid nanofiber interface layer modified on the surface; Wherein, the aramid nanofiber solution is prepared by the following steps: (a) Place PPTA and KOH in a beaker, add DMSO solution and deionized water, and stir; (b) continuing to add deionized water and stirring, filtering the stirred solution to collect the aramid nanofibers; (c) dispersing the aramid nanofibers in deionized water, vacuum filtering, collecting the aramid nanofibers and re-dispersing them in anhydrous ethanol, vacuum filtering again, and collecting the aramid nanofibers; repeating step (c) multiple times; (d) The collected aramid nanofibers are dispersed in anhydrous ethanol to obtain an aramid nanofiber solution.

2. The method for preparing a zinc metal material modified with an aramid nanofiber interface layer according to claim 1, characterized in that: In the step (1), the temperature of ultrasonic cleaning is 20-30°C, and the time of ultrasonic cleaning is 15-30 min; vacuum drying is adopted, the drying temperature is 45-60°C, and the drying time is 10-30 min.

3. The method for preparing a zinc metal material modified with an aramid nanofiber interface layer according to claim 1, characterized in that: The concentration of the aramid nanofiber solution in step (2) is 1.5-3 mg / mL.

4. The method for preparing a zinc metal material modified with an aramid nanofiber interface layer according to claim 1, characterized in that: The mass ratio of PPTA to KOH in the step (a) is 1:(1-3).

5. The method for preparing a zinc metal material modified with an aramid nanofiber interface layer according to claim 1 or 4, characterized in that: In the step (a), the mass volume ratio of PPTA to DMSO solution is 1 g: (400-600) ml, and the mass volume ratio of PPTA to deionized water is 1 g: (15-25) ml; in the step (b), deionized water is added in an amount of 2-3 times the volume of the DMSO solution, and the stirring time is 2-4 h.

6. The method for preparing a zinc metal material modified with an aramid nanofiber interface layer according to claim 1, characterized in that: In the steps (b) and (c), a filter membrane with a pore size of 0.22 µm is used.

7. A zinc metal material modified with an aramid nanofiber interface layer, characterized in that: The aramid nanofiber interface layer is prepared by the preparation method according to any one of claims 1 to 6, wherein the thickness of the aramid nanofiber interface layer is 1 to 3 µm, and the aramid nanofiber interface layer is a three-dimensional porous structure with abundant and uniform pores.

8. Use of the zinc metal material modified with the aramid nanofiber interface layer as claimed in claim 7 as a negative electrode material for aqueous zinc ion batteries.

9. The use of the zinc metal material modified with an aramid nanofiber interface layer as a negative electrode material for an aqueous zinc ion battery according to claim 8, characterized in that: The aqueous zinc ion battery is a zinc-zinc symmetrical battery, which comprises a zinc sheet positive electrode, a zinc sheet negative electrode, a ZnSO4 electrolyte and a glass fiber separator, wherein the zinc sheet negative electrode is punched out of a zinc metal material modified with an aramid nanofiber interface layer.

10. The use of the zinc metal material modified with an aramid nanofiber interface layer as a negative electrode material for an aqueous zinc ion battery according to claim 9, characterized in that: The aqueous zinc ion battery is obtained by the following steps: using a punching machine to punch the prepared zinc metal material modified with the aramid nanofiber interface layer into a pole piece with a diameter of 12 mm, and assembling it in the order of a negative electrode shell, a spring, a gasket, a negative electrode, a glass fiber separator of GF / D standard, a positive electrode, a gasket, and a positive electrode shell, wherein 80-100 μL of 2M ZnSO4 electrolyte is added to the separator, and a button battery is packaged into a button battery using a button battery packaging machine.

Citation Information

Patent Citations

  • Cathode material of lithium ion battery, its preparation method and lithium ion battery

    CN103887506A

  • Zinc negative electrode with zinc ion conductivity interface modification layer, battery and preparation method

    CN111933912A

  • Preparation method of aramid nanofiber-based battery membrane with micro-nano porous structure

    CN113506949A

  • Method for protecting metal negative electrode of aqueous battery by using hydrophobic organic layer

    CN113764652A

  • Lossless modification method for simultaneously improving ultraviolet radiation resistance and adhesive property of aramid fiber

    CN116377708A